A Comparative Study on the Health Status of Women in India and Kerala - K.A. Stephanson and Haseena Beevi A.A (Asian Journal of Research in Social Sciences and Humanities, 2015)
In every society the women community was not given due attention especially on the health aspect. In most societies, women are the most deprived sections from all the health facilities. They are the most affected groups right from conception to the end of their lives in terms of poor medical care during pregnancy, after delivery as a baby, as a girl, and as a woman. They suffer from poor nourishment, medical care, education and moral support. Women’s health involves their emotional, social and physical well being. It is determined by social, political, economic and biological factors. Health is concerned with qualitative improvement and it is not subject to exact measurement. The prevalent indices to measure health status are Death Rate, Infant Mortality Rate, incidence and prevalence of diseases, admission rates of patients to the hospitals, expectation of life and so on. Among these, mortality and life expectancy is the widely used measure of health status of a population. Morbidity may be a more useful indicator than mortality because it is related to pain and sufferings of the people while mortality is a terminal event (Chen, 1990). The commonly used measure of morbidity is self perceived illness prevalence rate defined as the number of persons per 1000 population reporting illness during the reference period.